Hotel De Palma Ampang / Husaini Aras Agus Salim - Agus Salim, Husaini Aras; Ariffin, Muhamad Azizan; Mohd Roji, Aelinawati; Arrifin, Syafawati; Daud, Lesanizan (2003)
De Palma Hotel Ampang is under manage by Marubi Hotel Management which formed in 1993. The company is headed by its Managing Director, Mohd IIyas Zainol Abidin who has been in the hotel industry in the last 28 years.